The Threat of The Covid-19 Pandemic And Military Aggression As Factors of Youth Migration - Grazyna KOWALEWSKA; Leslaw MARKOWSKI (Communications of International Proceedings, 2022)
Purpose: The article is a continuation of original, international research on Generations carried out in 2017 and 2020, and 2022 among young people, students of Management. They examined the tendency of young people to migrate. The purpose of the article below is to determine the impact of non-economic factors, including the Covid-19 pandemic and the threat of war related to the inclination to migrate. Due to the fact that the research is still ongoing, and the full data has been received only from Poland, the article is limited to the analysis of trends among Polish students from universities that participated in previous rounds of research. Design/Methodology/Approach: The study of the influence of the distinguished factors on the propensity to migrate was based on logistic binomial regression. The estimates made it possible to verify the hypotheses posed in the study. Results: As a result of the research, it was found that the fear of contracting COVID-19 and the spread of conflict (war) has a negative effect, while vaccination against COVID-19 has a positive effect on the tendency of young people to migrate. Practical Implications: The study will determine how the propensity to migrate young people has evolved during the uncertainty surrounding the Covid-19 pandemic and hostilities/ terrorist attacks.
Keywords: migration; students; COVID-19; war.